Praktik Suasana Religiu dalam Perspektif Kampus Islami: Studi pada Mahasiswa Pendidikan Agama Islam Fakultas Tarbiyah IAIN Curup - Deri Wanto; Muhammad Idris (At Turots: Jurnal Pendidikan Islam, 2024)
Basically, the spiritual needs found in humans, both religious and non-religious individuals, certainly every human being has a natural tendency to be religious towards religious beliefs, so it is very important to foster a religious environment to achieve Islamic goals in national education. The aim of this research is to determine the understanding of Islamic religious education study program students regarding religious concepts from an Islamic campus perspective, the practice of the religious atmosphere of students in the PAI IAIN Curup study program, and the supporting factors for the atmosphere of students in the IAIN Curup study program. The research method used is qualitative research using a phenomenological approach and data collection obtained is by observation and interviews. The results of this research show that PAI study program students understand religious concepts from an Islamic perspective, namely PAI students certainly realize the importance of understanding religious concepts in the context of an Islamic campus, especially in shaping student character and ethics. Then practice the religious atmosphere of IAIN Curup PAI study program students by cultivating religious values of religion by having a religious vision and mission, implementing integrative learning, creating a religious atmosphere and following traditions and behavior consistently. And there are also factors supporting the religious atmosphere of IAIN Curup PAI study program students, namely an academic environment that is quite supportive, lecturers who provide qualified guidance, adequate infrastructure, and the existence of religious programs/organizations.